PERAN GURU PAI DALAM MENGEMBANGKAN KREATIVITAS PEMBELAJARAN MELALUI TEKNOLOGI DIGITAL DI MTS I’ANATUT THOLIBIN - Novitasari, Lenny; Putri, Nabila (Fakultas Agama Islam, 2025)
The role of Islamic Religious Education (PAI) teachers at MTs I'anut Tholibin is very important in developing learning The role of Islamic Religious Education (PAI) teachers at MTs I'anut Tholibin is very important in developing learning utilize technology as a tool to increase student interaction and understanding of teaching material. By using digital media, teachers can create more interesting and interactive learning experiences, which encourage students to actively participate. Teacher creativity in designing technology-based teaching materials not only helps achieve learning goals, but also develops 21st century skills in students, such as critical thinking and collaboration. However, challenges such as lack of training and access to technology must be overcome so that technology utilization can be optimal. Therefore, support from the school in the form of training and providing technological facilities is very necessary. In this way, PAI teachers act as facilitators who are able to inspire students through innovation in digital learning.